1966
DOI: 10.1128/aem.14.1.49-54.1966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Chloride and pH on the Outgrowth of Spores of Type E Clostridium botulinum at Optimal and Suboptimal Temperatures1

Abstract: SEGNER, W. P. (Continental Can Co., Inc., Chicago, Ill.), C. F. SCHMIDT, AND J. K. BOLTZ. Effect of sodium chloride and pH on the outgrowth of spores of type E Clostridium botulinum at optimal and suboptimal temperatures. Appl. Microbiol. 14:49-54. 1966.-The sodium chloride inhibition of spore outgrowth of four strains of type E Clostridium bolulinum was determined in a Trypticase-peptoneglucose (TPG) medium. At 16, 21, and 30 C, spores of three strains required 5.0% and one strain 4.5% salt for complete inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…In total aerobic mesophile group, the microbial reduction attained, on average, 0.4 and 0.8 log 10 CFU mL À1 for 1 and 2.5 mg PPE per mL (P < 0.01), while for total aerobic psychrophiles the microbial reductions were about 0.2 and 0.6 log 10 CFU mL À1 , respectively (P < 0.01). Despite the clear reduction of microbial loads in treated and fortified juices, further microbiological safety studies should be conducted, especially concerning the germination of spores of Clostridium botulinum type E (Segner et al, 1966). As a low-acid beverage, carrot juice can pose a risk of botulism poisoning even after pasteurisation since lower processing temperatures could not be sufficient to eliminate spores of Clostridium botulinum; temperature abuse conditions during storage could also lead to toxin production in pasteurised carrot juices (FDA, 2007).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…In total aerobic mesophile group, the microbial reduction attained, on average, 0.4 and 0.8 log 10 CFU mL À1 for 1 and 2.5 mg PPE per mL (P < 0.01), while for total aerobic psychrophiles the microbial reductions were about 0.2 and 0.6 log 10 CFU mL À1 , respectively (P < 0.01). Despite the clear reduction of microbial loads in treated and fortified juices, further microbiological safety studies should be conducted, especially concerning the germination of spores of Clostridium botulinum type E (Segner et al, 1966). As a low-acid beverage, carrot juice can pose a risk of botulism poisoning even after pasteurisation since lower processing temperatures could not be sufficient to eliminate spores of Clostridium botulinum; temperature abuse conditions during storage could also lead to toxin production in pasteurised carrot juices (FDA, 2007).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…The concentration of NaCl permitting microbial growth generally decreases as storage temperature decreases (Table ll); or, a given NaCl concentration delays microbial growth longer at lower storage temperatures (Segner et al 1966;Ohye and Christian 1967;Alford and Palumbo 1969;Emodi and Lechowich 1969;Baird-Parker and Baillie 1973;Ingram 1973;Hauschild 1982). Pivnick and Barnett (1965) reported that with (1966) 2.2% NaCl in bologna, C. botulinum toxin was not produced for two months at 20°C or one month at 25"C, while the samples were toxic in one week at 30°C.…”
Section: Storage Temperaturementioning
confidence: 99%
“…botulinum types A and B : however, type E is inhibited by 6 5 % of salt (Spencer, 1967). It has also been shown that salt concentrations which have no effect on spore outgrowth a t temperatures near optimum can extend the outgrowth time significantly a t low temperatures (Segner, Schmidt, & Boltz, 1966;Emodi & Lechowich, 1969). This fact is undoubtedly important for semi-preserved meats that require refrigeration in order to maintain product stability.…”
Section: (B) Initiation Of Germination and Outgrowthmentioning
confidence: 99%